IMPLEMENTASI PEMBELAJARAN IPS TERHADAP PEMBENTUKAN KARAKTER SISWA DI SEKOLAH DASAR - Safinaz Sahira; Rejeki Rejeki; Miftahul Jannah; Rinda Gustari; Yuli Asnita Nasution; Sulis Windari; Seri Mulia Reski (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
Social Sciences (IPS) is a subject that has an important role in forming good citizens, so learning Social Sciences (Social Studies) is very important at the basic education level where basic education is the foundation of understanding and knowledge about how to live socialize in society. This study aims to obtain the implementation of social studies learning towards the formation of students' character in elementary schools. This research was conducted in Rokan Hulu Regency, which is located at SD Negeri 010 Rambah on December 11, 2021. Using qualitative descriptive research methods. Sources of data obtained are primary data and secondary data with data collection techniques namely observation, interviews, and documentation. The subjects in this study were teachers in elementary schools. The results of this study can determine the character is an individual trait, a person's personality, character and behavior that a person has in a person's life. Character is the main aspect in shaping a person's quality to be a noble person. Social studies education plays an important role in producing quality students, namely humans who are able to think critically, creatively, logically, and take the initiative in dealing with social symptoms and problems that develop in society.